CompTIA A+ complete video course (220-901) (LiveLessons (Indianapolis, Ind.), 2016)
"CompTIA A+ 220-901 Complete Video Course is a unique video product that provides a solid understanding of A+ skills. The purpose of these videos is to act as quick, concise, hands-on training that is easily absorbed. The modules in this course cover every objective in the CompTIA A+ 220-901 exam and can be used as your sole resource for learning the material needed to study for and pass the test. You can also use this as a supplement to other A+ training. There are a total 4 modules that map to the main objectives of the CompTIA A+ 220-901 exam. These modules contain 34 lessons with video totaling over 21 hours of hands-on demonstrations, audio instruction, animations, whiteboard training, and video screencasting. The videos also include the author building a computer live on camera so you can see first-hand how to accomplish this key task. He also includes hands-on configuration labs; laptop, smartphone and device hardware labs; and live-action troubleshooting labs."--Resource description page.